2017
DOI: 10.1111/bdi.12560
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted cortico‐limbic connectivity during reward processing in remitted bipolar I disorder

Abstract: Objectives Bipolar disorder (BD) is associated with elevated reward sensitivity and persistent positive affect, yet the neural mechanisms underlying these patterns are not well understood. In the present study, we examined putative disruptions in communication within a well-known corticolimbic reward circuit during reward processing as a potential contributing mechanism to these symptoms. Methods The present investigation employed a within- and between-subjects design utilizing a monetary and social incentiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 87 publications
(131 reference statements)
1
23
0
Order By: Relevance
“…Another important finding of the current study is that a history of childhood trauma is associated with enhanced functional connectivity between the left amygdala and dorsal and ventral striatum in cocaine users, whereas it is associated with reduced functional connectivity between the left amygdala and the dorsal and ventral striatum in non-drug using controls. While reduced amygdala-striatal connectivity has been suggested to underlie reduced risk aversion in healthy participants ( 50 ), increased amygdala-striatal connectivity has been previously demonstrated in pathological gamblers ( 70 ) and patients with bipolar disorder ( 71 ) during reward processing, whereas the control groups in these studies consistently showed reduced amygdala-striatal connectivity during the processing of reward ( 70 , 71 ). Since the amygdala regulates reward-related signaling in the striatum ( 72 ) and inhibiting amygdala-striatal connectivity impairs reward seeking in rodents ( 73 ), enhanced amygdala-striatal connectivity during reward processing may underlie impulsive decision making ( 70 ).…”
Section: Discussionmentioning
confidence: 94%
“…Another important finding of the current study is that a history of childhood trauma is associated with enhanced functional connectivity between the left amygdala and dorsal and ventral striatum in cocaine users, whereas it is associated with reduced functional connectivity between the left amygdala and the dorsal and ventral striatum in non-drug using controls. While reduced amygdala-striatal connectivity has been suggested to underlie reduced risk aversion in healthy participants ( 50 ), increased amygdala-striatal connectivity has been previously demonstrated in pathological gamblers ( 70 ) and patients with bipolar disorder ( 71 ) during reward processing, whereas the control groups in these studies consistently showed reduced amygdala-striatal connectivity during the processing of reward ( 70 , 71 ). Since the amygdala regulates reward-related signaling in the striatum ( 72 ) and inhibiting amygdala-striatal connectivity impairs reward seeking in rodents ( 73 ), enhanced amygdala-striatal connectivity during reward processing may underlie impulsive decision making ( 70 ).…”
Section: Discussionmentioning
confidence: 94%
“…Similar with patients with orbitofrontal cortex damage (Bechara et al, ), patients with BD also showed a disability to take frequency and magnitude of punishments into account at the same time appropriately. The hypersensitivity to magnitude, especially for gains (Dutra, Man, Kober, Cunningham, & Gruber, ), further led to a failure to weigh immediate versus future consequences of choices precisely, which might be one of the reasons for decision‐making impairment. Our study did not find significant insensitivity to punishments in the BD group.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies have revealed the increased functional connections of the amygdala, medial prefrontal cortex, and ventrolateral prefrontal cortex and a decreased connectivity between the medial prefrontal and cingulate cortices (6)(7)(8). The enhanced connectivity of the ventral striatum seed area with the orbitofrontal cortex and amygdala has also been reported in reward processing reception in remitted BD type I (9,10). The analytical techniques used in these neuroimaging studies are FC analysis and independent component analysis (ICA) that are efficient in exploring the function of brain networks but not local brain activities.…”
Section: Introductionmentioning
confidence: 96%
“…Many neuroimaging studies have been performed to improve the accuracy of the diagnosis of BD. Despite the mixed results, some brain regions have been identified to present abnormal activities and functional connectivity (FC) (6)(7)(8)(9)(10). Three studies have revealed the increased functional connections of the amygdala, medial prefrontal cortex, and ventrolateral prefrontal cortex and a decreased connectivity between the medial prefrontal and cingulate cortices (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%